Composição de Lepidoptera (Papilionoidea e Hesperioidea) do Rio Grande do Sul e variabilidade espaço-temporal em três áreas no norte do estado, Brasil - Giovenardi, Ricardo (2014)
In order to contribute to the knowledge of butterflies in the Rio Grande do Sul, works related with bionomics, taxonomy and forest inventory were consulted and it was found the spatiotemporal variability of butterflies in three fragments in the northern of the State. On accumulated studies, it was found 832 species and subspecies. After 1970, the papers published about butterflies increased almost exponentially and since 1990, also showed increase. The richest family is Hesperiidae with 357 (42.90%) species and subspecies, followed by Nymphalidae with 227 (27.28%), Lycaenidae with 94 (11.30%), Riodinidae with 80 (9.62%), Pieridae with 43 (5.17%) and Papilionidae with 31 (3.73%). Between physiographic regions, the Depressão Central showed 495 (59.50%) species and subspecies recorded (more richness) and the Encosta Superior do Nordeste presented 17 (2.04%) species and subspecies (less richness). The distribution of inventories shows that in Rio Grande do Sul there are still areas that lack information about butterflies. In the study about spatiotemporal variability, was created a list of species of butterflies of the Parque Estadual do Turvo (PET), Reserva Indígena de Iraí (RII) and Reserva Biológica Municipal Moreno Fortes (REBMF). Bimonthly field trips were performed from november 2010 to october 2012. After 580 hours net-sampling, 4999 individuals were registered, distributed in 280 species / subspecies of butterflies. Tegosa claudina (Eschscholtz, 1821), Dynamine myrrhina (Doubleday, 1849), Heliconius ethilla narcaea (Godart, 1819) and Heliconius erato phyllis (Fabricius, 1775), were the most abundant species. The road with access to the Porto Garcia (PG) was the richest and the road with access to Salto Yucumã (SY) showed the greatest abundance, both located in PET. Only 29.64% of the species were recorded in only one forest fragment. The correlations of the richness of butterflies with temperature and rainfall not demonstrated statistical significant. Cluster analysis and MANOVA showed that the fauna of the sampling united formed separate groups. Dione juno suffumata Brown & O. Mielke, 1972, Anteos clorinde (Godart, [1824]) and Panthiades phaleros (Linnaeus, 1767) are new records for Rio Grande do Sul.